Dynamics of Digital Transformation of Organizations in the Russian Federation - Pavel E. Prokhorov (Статистика и экономика, 2021)
Analysis of the use of information and communication technologies in organizations makes it possible to determine the speed and intensity of the digital transformation of the economy. In previous studies, specialists evaluated the dynamics of ICT use in organizations using a small range of indicators in the short term. In this study, the analysis of the dynamics of the use of ICT in organizations was carried out for a wide range of indicators in the long term. Based on this approach, I have identified the patterns of digital transformation and the stage of digital maturity of the economy.Purpose of the study. The purpose of this study is to analyze trends in the digital transformation of the Russian economy. To achieve this goal, I calculated the indicators of the speed and intensity of the level of ICT use in the activities of organizations for certain types of technologies.Materials and methods. I analyzed the dynamics of indicators that characterize: the use of Internet access, business process automation systems, websites and EDI systems, and e-commerce. To analyze the dynamics, I used information from surveys of the Federal State Statistics Service. Indicators are presented in annual frequency for 2005-2019 for the Russian Federation.Results. I found that the peculiarity of the current stage of digital maturity of organizations lies in reaching the limits of the spread of the Internet. For 2010-2019 the average annual growth rate of the share of organizations using the Internet was 1.1%. One of the main directions of digital transformation is the automation of the organization’s business processes. However, the potential for automation has been unevenly realized in a number of areas. The share of organizations using CRM, ERP, SCM - systems increased 2.7 times in 2010-2019, to 20.5%. At the same time, the share of organizations using electronic document management increased by 13% over the same period, to 70% in 2019. At the current stage of digital maturity, organizations are showing a high level of participation in e-commerce. The increase in the share of organizations placing orders for goods and services was 23.7%, and the increase in the share of organizations that make settlements with suppliers of ordered goods and services - up to 93%. Also digital economic activity has expanded, the value of data has increased, and this has been reflected in the use of the Internet for the exchange of electronic products.Conclusion. The results of the analysis can be used in studies on modeling and forecasting trends in digital transformation. The findings of the study on trends in the use of ICT in organizations can be useful for a deeper and more comprehensive study of the nature of the dynamics and patterns of development of digital transformation.